Regularity Criteria for Hyperbolic Navier-Stokes and Related System. (6th September 2012) - Fan, Jishan; Ozawa, Tohru
Abstract : We prove a regularity criterion for strong solutions to the hyperbolic Navier-Stokes and related equations in Besov space.